Digital Media and the Reconfiguration of Local Culture in Indonesia - Rahmi Setiawati (West Science Social and Humanities Studies, 2026)
The rapid development of digital technology has significantly influenced the way local cultures are represented, preserved, and transformed in contemporary society. In Indonesia, digital media has created new opportunities for cultural communities to disseminate local traditions, strengthen cultural awareness, and engage younger generations in cultural preservation efforts. However, the increasing integration of digital platforms also introduces challenges related to cultural adaptation, authenticity, and changes in cultural identity. This study aims to analyze the influence of digital media on the reconfiguration of local culture in Indonesia. A quantitative research approach was applied using survey data collected from 200 respondents who actively engage with digital media platforms and have experience accessing local cultural content online. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The analysis involved validity testing, reliability testing, descriptive statistical analysis, classical assumption testing, and simple linear regression analysis. The results indicate that digital media has a positive and significant influence on local cultural reconfiguration. Furthermore, the coefficient of determination (R² = 0.468) indicates that digital media utilization explains 46.8% of the variation in local cultural reconfiguration. These findings demonstrate that digital media functions not only as a communication platform but also as an important mechanism for cultural preservation, adaptation, and identity reconstruction. This study contributes to understanding how technological development influences cultural sustainability in Indonesia and highlights the importance of utilizing digital platforms strategically to maintain cultural values while encouraging innovation.